Microbubbles as a vehicle for gene and drug delivery: current clinical implications and future perspectives - Geis, Nicolas; Katus, Hugo; Bekeredjian, Raffi (Current pharmaceutical design, 2012)
Ultrasound targeted microbubble destruction (UTMD) has evolved as a novel system for non-invasive, organ- and tissuespecific drug and gene delivery